Studies in the oxidation of methane; and, in the thermal decomposition of formaldehyde - Prot, Jan (The University of Edinburgh, 1948)
1) The Slav oxidation of methane was studied by a flow method in the range of temperatures between SOCAC and 750°C

2) The hope that by subjecting methane mixed with nitrogen and oxygen to a high temperature for a very short tine and by cooling the products of oxidation immediately the greater part of the methane would be transformed into formaldehyde was not. followed by success. The yields of formaldehyde were very low and aid not exceed 0.8 % of the methane passed through the furnace.

3) Many of the experimental results were erratic The passing of methane or oxygen through the heated furnace removed this difficulty.

4) Methane was oxidized in a mixture with nitrogen and oxygen in the ratio N₂:O₂:CH₄ -2.1.1 and 2.0.1:1 respectively. The decreasing of oxygen in these mixtures had only a small effect on the oxidation products.

5) hater vapour added to the gas mixtures before the reaction, increased markedly the rate of oxidation.

5) The presence cf hydrogen in the final products is probably due to the decomposition of methane by steam.

7) The thermal decomposition of formaldehyde was also studied by the same flow method and by means of the furnace used in previous experiments.

8) The experiments were carried out both when the furnace was empty and when it was filled with pumice grains. The rate of decomposition was greater when the furnace was filled with pumice.

9) Formaldehyde decomposes very quickly at temperatures between 750° and 700°C and relatively slowly below 400° or 500°U. Between 700°C and 450°C the effect of temperature on the velocity constant for decomposition of formaldehyde in the furnace filled with pumice can be represented by the simple equation:

K = 0.01439t - 6.294

while that in the empty furnace and in the range of temperature between 700°G and 500°G can be expressed by the equation

K₁ = 0.016622t - 8.224.

10) In the lower temperature region the thermal decomposition of formaldehyde itself is not mainly responsible of the low yield of formaldehyde in the methane oxidation.

11) General considerations on the mechanism of the slow oxidation of methane have been given.